Annealing technology of anchor chain steel

By using specific cleaning liquid and heat treatment technology before annealing the anchor chain steel, the problem of many impurities on the surface of the anchor chain steel is solved, the annealing effect and quality are improved, and a more uniform and efficient annealing process is achieved.

CN119639997APending Publication Date: 2025-03-18HEBEI SHENGJIA PRECISION MASCH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411541925.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The anchor chain steel is not thoroughly cleaned before annealing, resulting in a lot of surface impurities, affecting the annealing effect and quality.

Method used

The anchor chain steel is cleaned with a specific cleaning solution, including sodium hydroxide, diethylenetriamine pentaacetic acid, sodium citrate, sodium gluconate, alcohol ether glycosides and complexes (sophora, rhamnolipid and modified diatomaceous earth compound), and heat treatment is carried out under a nitrogen atmosphere.

Benefits of technology

Effectively remove grease, emulsion and other dirt on the surface of the anchor chain steel, improve the uniformity and efficiency of annealing, improve the microstructure, enhance strength and toughness, and thus improve the quality of the anchor chain steel.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119639997A_ABST
    Figure CN119639997A_ABST
Patent Text Reader

Abstract

The invention discloses an annealing technology of anchor chain steel, which comprises the following steps: putting the anchor chain steel into a cleaning solution for cleaning, then washing with water, and drying to obtain the cleaned anchor chain steel; the anchor chain steel is subjected to heat treatment, the temperature is increased to 300-400 DEG C firstly, heat preservation is conducted, the temperature is increased to 550-750 DEG C for the second time, heat preservation is conducted, the temperature is increased to 900-950 DEG C again, heat preservation is conducted, quenching is conducted to the room temperature through saline water, the temperature is increased to 300-400 DEG C through tempering, heat preservation is conducted, the temperature is increased to 500-600 DEG C through secondary tempering, heat preservation and water cooling are conducted, and the anchor chain steel subjected to heat treatment is obtained; the cleaning solution in the step S1 comprises the following raw materials in parts by weight: 20-35 parts of sodium hydroxide, 5-9 parts of diethylene triamine pentaacetic acid, 1-3 parts of sodium citrate, 1-5 parts of sodium gluconate, 6-12 parts of alkyl ethoxy polyglycosides, 11-18 parts of a compound and 150-200 parts of water, and the compound is formed by compounding sophorolipid, rhamnolipid and modified diatomite. The technical problem that anchor chain steel is low in quality is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of anchor chain steel production, and in particular relates to an annealing technology for anchor chain steel. Background Art

[0002] Anchor chain refers to a special chain that connects the anchor and the hull and transmits the anchor's grip. Anchor chain is an important facility related to the safety of ocean-going, offshore and inland ships. Anchor chain is made up of many links. Depending on whether there is a stay in the middle of the link, it is divided into stay anchor chain and no stay anchor chain. Anchor chain can be made by forging, casting and welding. Marine anchor chain consists of several sections, each section is 25-27.5 meters long, and the sections are connected by chain links or shackles.

[0003] The anchor chain is a chain connecting the anchor and the hull. It is used to transmit and buffer the external force on the ship. It is generally made of steel. The anchor chain steel needs to go through a variety of processing processes during the production and processing. Among them, annealing technology is very important, which determines the final quality of the anchor chain steel. Some anchor chain steels are not cleaned thoroughly before annealing, resulting in more impurities on the surface of the anchor chain steel, which will affect the annealing effect and thus affect the quality of the anchor chain steel. Summary of the invention

[0004] The invention provides an annealing technology for anchor chain steel, which is used to solve the technical problem of low quality of existing anchor chain steel.

[0005] In view of this, the present invention provides an annealing technology for anchor chain steel, comprising the following steps:

[0006] S1: putting the anchor chain steel into a cleaning solution for cleaning, then rinsing with water, and drying to obtain the cleaned anchor chain steel;

[0007] S2: heat treating the anchor chain steel, first heating it to 300-400°C, keeping it warm, heating it to 550-750°C for the second time, keeping it warm, then heating it to 900-950°C, keeping it warm, quenching it with salt water to room temperature, then tempering it to 300-400°C, keeping it warm, tempering it to 500-600°C for the second time, keeping it warm, and water cooling it to obtain the heat-treated anchor chain steel;

[0008] Among them, the cleaning solution in step S1 includes the following raw materials in parts by weight: 20-35 parts of sodium hydroxide, 5-9 parts of diethylenetriaminepentaacetic acid, 1-3 parts of sodium citrate, 1-5 parts of sodium gluconate, 6-12 parts of alcohol ether glycoside, 11-18 parts of the complex, and 150-200 parts of water, and the complex is a compound of sophorolipids, rhamnolipids and modified diatomaceous earth.

[0009] Furthermore, an annealing technology for anchor chain steel comprises the following steps:

[0010] S1: putting the anchor chain steel into a cleaning solution for cleaning, then rinsing with water, and drying to obtain the cleaned anchor chain steel;

[0011] S2: heat-treating the anchor chain steel, first heating it to 300-400°C, keeping it warm for 40-60min, heating it to 550-750°C for the second time, keeping it warm for 40-60min, heating it to 900-950°C for the second time, keeping it warm for 50-70min, quenching it with salt water to room temperature, then tempering it to 300-400°C, keeping it warm for 45-65min, tempering it to 500-600°C for the second time, keeping it warm for 55-75min, and cooling it with water to obtain the heat-treated anchor chain steel;

[0012] Among them, the cleaning solution in step S1 includes the following raw materials in parts by weight: 20-35 parts of sodium hydroxide, 5-9 parts of diethylenetriaminepentaacetic acid, 1-3 parts of sodium citrate, 1-5 parts of sodium gluconate, 6-12 parts of alcohol ether glycoside, 11-18 parts of the complex, and 150-200 parts of water, and the complex is a compound of sophorolipids, rhamnolipids and modified diatomaceous earth.

[0013] Optionally, the composite is prepared by the following method: placing modified diatomaceous earth in water, ultrasonically dispersing, and mixing evenly to obtain a first mixed solution; placing sophorolipid in water, adding rhamnolipid, and mixing evenly to obtain a second mixed solution; mixing the first mixed solution and the second mixed solution evenly, standing, filtering, washing, and drying to obtain a composite.

[0014] Furthermore, the composite is prepared by the following method: placing the modified diatomaceous earth in water, ultrasonically dispersing for 20-40 minutes, and mixing evenly to obtain a first mixed solution; placing the sophorolipid in water, adding rhamnolipid, and mixing evenly to obtain a second mixed solution; mixing the first mixed solution and the second mixed solution evenly, standing for 1-2 hours, filtering, washing, and drying to obtain a composite;

[0015] The amount of water added to each gram of modified diatomaceous earth is 3-5 mL, and the amount of water added to each gram of sophorolipid is 4-6 mL.

[0016] Optionally, the weight ratio of the sophorolipid, rhamnolipid and modified diatomaceous earth is 1:(0.8-1.3):(4-7).

[0017] Optionally, the modified diatomite is prepared by the following method: sodium hydroxide and aluminum hydroxide are put into water, mixed evenly, heated and reacted to obtain a mixed solution A; diatomite is put into water, mixed evenly, heated and reacted to obtain a mixed solution B; mixed solution A and mixed solution B are mixed evenly, heated and reacted, filtered, washed, and dried to obtain modified diatomite.

[0018] Furthermore, the modified diatomite is prepared by the following method: sodium hydroxide and aluminum hydroxide are put into water, mixed evenly, heated to 80-100°C, and reacted for 1-2h to obtain a mixed solution A; diatomite is put into water, mixed evenly, heated to 80-100°C, and reacted for 1-2h to obtain a mixed solution B; mixed solution A and mixed solution B are mixed evenly, heated to 80-100°C, reacted for 4-8h, filtered, washed with water 3-5 times, and dried to obtain modified diatomite;

[0019] The amount of water added to each 1g of the total weight of sodium hydroxide and aluminum hydroxide is 1-3mL, the weight ratio of sodium hydroxide to aluminum hydroxide is 1:1, and the amount of water added to each 1g of diatomaceous earth is 5-8mL.

[0020] Optionally, the sophorolipid and rhamnolipid are pretreated by the following method before use: put the sophorolipid and rhamnolipid into water, adjust the pH value, heat and heat, stir in a water bath, stand and separate, take out the lower layer, repeat the above operation multiple times to obtain the pretreated sophorolipid and rhamnolipid.

[0021] Furthermore, the sophorolipids and rhamnolipids are pretreated by the following method before use: the sophorolipids and rhamnolipids are placed in water, the pH value is adjusted to 5 with sodium hydroxide solution, the temperature is raised to 40-60° C., stirred in a water bath, allowed to stand for stratification, the lower layer is taken out, and the above operation is repeated multiple times to obtain the pretreated sophorolipids and rhamnolipids;

[0022] The amount of water added to the total weight of 1g of sophorolipid and rhamnolipid is 4-6mL, and the weight ratio of sophorolipid to rhamnolipid is 1:1.

[0023] Optionally, in step S1, the specific cleaning process of the anchor chain steel in the cleaning liquid is: first immersing for 5-10 minutes, and then swing washing for 1-5 minutes, wherein the swing frequency is 25-45 times / min, the round trip is 1 time, and the swing distance is 40-60mm.

[0024] Optionally, the anchor chain steel in step S2 is heat treated in an atmosphere of a protective gas, wherein the protective gas is hydrogen or nitrogen.

[0025] Optionally, the mass fraction of the brine in step S2 is 5-10%.

[0026] It can be seen from the above technical solutions that the embodiments of the present invention have the following advantages:

[0027] 1. The present application first uses a cleaning liquid to clean the anchor chain steel, and then heat treats it, which can remove grease, emulsion and other dirt on the surface of the anchor chain steel, reduce impurities on the surface of the anchor chain steel, and enable it to absorb heat more effectively during the annealing process, improve the uniformity and efficiency of annealing, and help improve the microstructure of the anchor chain steel, enhance the strength and toughness of the anchor chain steel, and thus improve the quality; wherein, sodium hydroxide is a strong alkali, which can undergo saponification reaction with grease, and can also react with oxides on the surface of the anchor chain steel; diethylenetriaminepentaacetic acid can remove metal ions on the surface of the anchor chain steel, sodium citrate and sodium gluconate are chelating agents, which can form stable chelates with metal ions on the surface of the anchor chain steel, and also have an emulsifying effect, which is helpful for the removal of grease; alcohol ether glycoside is a nonionic surfactant, which has good emulsifying, dispersing and wetting properties, can effectively reduce the surface tension of water, and further improve the cleaning effect of other ingredients on the anchor chain steel;

[0028] The complex is composed of sophorolipids, rhamnolipids and modified diatomaceous earth. Sophorolipids have excellent solubilizing and emulsifying properties, and can effectively disperse and dissolve organic substances such as oil and fat on the surface of the anchor chain steel; rhamnolipids can significantly reduce the oil-water interfacial tension, making it easier for oil to separate from the surface of the anchor chain steel and enter the cleaning liquid, which helps to improve the thoroughness and efficiency of cleaning; modified diatomaceous earth has a large specific surface area and has better adsorption properties; through the compounding of the three, sophorolipids and rhamnolipids can be loaded on the modified diatomaceous earth. Sophorolipids and rhamnolipids, as surfactants, can reduce the surface tension of water and improve the wettability of water to grease, while the modified diatomaceous earth has good adsorption properties and can adsorb grease and impurities. When used in combination, sophorolipids and rhamnolipids can first penetrate and emulsify dirt such as grease, and the modified diatomaceous earth then adsorbs the emulsified dirt such as grease. Under the joint action, the cleaning effect on the anchor chain steel is improved; in addition, the surface activity of sophorolipids and rhamnolipids helps to improve the dispersibility of the modified diatomaceous earth in water, avoids the agglomeration of the modified diatomaceous earth particles, facilitates them to play a greater role, helps to improve the cleaning effect on the anchor chain steel, thereby facilitating annealing and helping to improve the quality of the anchor chain steel.

[0029] 2. The present application adopts sodium hydroxide and aluminum hydroxide to modify diatomaceous earth to obtain modified diatomaceous earth, which can improve the internal structure of diatomaceous earth, increase porosity, and increase specific surface area, thereby further improving adsorption capacity and reaction activity, making it easier to adsorb impurities and clean anchor chain steel.

[0030] 3. The present application pre-treats and purifies sophorolipids and rhamnolipids, thereby improving the purity of the two, making it easier for the two to play their roles, improving the cleaning effect on anchor chain steel, and reducing the impact on the annealing process, thereby helping to improve the quality of anchor chain steel. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] The present invention is further described in detail below with reference to the accompanying drawings and embodiments.

[0032] Figure 1 It is a schematic diagram of the anchor chain steel annealing technology of the present invention. DETAILED DESCRIPTION

[0033] In order to make the technical scheme of the present invention better understood by the personnel of the technical field, the technical scheme in the embodiment of the present invention is clearly and completely described below. Obviously, the described embodiment is only a part of the embodiment of the present invention, rather than all the embodiments. Based on the embodiment in the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present invention. Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or can be prepared by existing methods.

[0034] The alcohol ether glycoside is AEG330.

[0035] Preparation Example

[0036] Preparation Example 1

[0037] A modified diatomaceous earth is prepared by the following method:

[0038] Put 2kg of sodium hydroxide and 2kg of aluminum hydroxide into 8L of water, mix evenly, heat to 90°C, and react for 1.5h to obtain mixed solution A; put 2kg of diatomaceous earth into 13L of water, mix evenly, heat to 90°C, and react for 1.5h to obtain mixed solution B; mix mixed solution A and mixed solution B evenly, heat to 90°C, react for 6h, filter, wash with water 5 times, and dry to obtain modified diatomaceous earth.

[0039] Preparation Example 2

[0040] A composite is prepared by the following method:

[0041] 8 kg of the modified diatomaceous earth prepared in Preparation Example 1 was put into water, ultrasonically dispersed for 30 min, and mixed evenly to obtain a first mixed solution; 2 kg of sophorolipid was put into water, 1.6 kg of rhamnolipid was added, and mixed evenly to obtain a second mixed solution; the first mixed solution and the second mixed solution were mixed evenly, allowed to stand for 2 h, filtered, washed, and dried to obtain a composite;

[0042] The amount of water added to each 1g of modified diatomaceous earth is 4mL, and the amount of water added to each 1g of sophorolipid is 5mL.

[0043] Preparation Example 3

[0044] A composite, which is different from Preparation Example 2 in that the amount of rhamnolipid added in the composite is different, and the amount of rhamnolipid added in Preparation Example 3 is 2 kg.

[0045] Preparation Example 4

[0046] A composite, which is different from Preparation Example 2 in that the amount of rhamnolipid added in the composite is different, and the amount of rhamnolipid added in Preparation Example 4 is 2.6 kg.

[0047] Preparation Example 5

[0048] A composite, which is different from Preparation Example 2 in that the amount of modified diatomaceous earth added in the composite is different, and the amount of modified diatomaceous earth added in Preparation Example 5 is 11 kg.

[0049] Preparation Example 6

[0050] A composite material, which is different from Preparation Example 2 in that the amount of modified diatomaceous earth added in the composite material is different, and the amount of modified diatomaceous earth added in Preparation Example 6 is 14 kg.

[0051] Example

[0052] Example 1

[0053] An annealing technology for anchor chain steel comprises the following steps:

[0054] S1: Put the anchor chain steel into the cleaning liquid and immerse it for 8 minutes, then wash it for 3 minutes, where the swing frequency is 30 times / min, the round trip is 1 time, and the swing distance is 50mm, then rinse it with water and dry it to obtain the cleaned anchor chain steel;

[0055] S2: The anchor chain steel is heat treated in a nitrogen atmosphere, firstly heated to 350°C, kept warm for 50 minutes, then heated to 600°C for 50 minutes, then heated to 930°C for 60 minutes, quenched to room temperature with 8% brine, then tempered to 350°C, kept warm for 50 minutes, then tempered to 550°C for 60 minutes, cooled with water, and the heat-treated anchor chain steel is obtained;

[0056] The raw material ratio of the cleaning solution is shown in Table 1, and the composite in the cleaning solution is prepared by Preparation Example 2.

[0057] Table 1 Weight of each raw material of cleaning liquid (kg)

[0058]

[0059] Examples 9-12

[0060] An annealing technology for anchor chain steel, which differs from Example 7 in that the sources of the composite in the cleaning solution are different, and the composites in Examples 9-12 are prepared using Preparation Examples 3-6, respectively.

[0061] Example 13

[0062] An annealing technology for anchor chain steel, which is different from Example 11 in that the sophorolipids and rhamnolipids in the composite are pretreated by the following method before use: the sophorolipids and rhamnolipids are put into water, the pH value is adjusted to 5 with sodium hydroxide solution, the temperature is raised to 50°C, stirred in a water bath, allowed to stand for stratification, the lower layer is taken out, and the above operation is repeated multiple times to obtain the pretreated sophorolipids and rhamnolipids; wherein the amount of water added to the total weight of 1g of sophorolipids and rhamnolipids is 5mL, and the weight ratio of sophorolipids to rhamnolipids is 1:1.

[0063] Comparative Example

[0064] Comparative Example 1

[0065] An annealing technology for anchor chain steel, which is different from Example 1 in that no composite material is added to the raw materials of the cleaning liquid.

[0066] Comparative Example 2

[0067] An annealing technology for anchor chain steel, which differs from Example 1 in that the sophorolipids in the composite are replaced by rhamnolipids in equal amounts.

[0068] Comparative Example 3

[0069] An annealing technology for anchor chain steel, which differs from Example 1 in that the modified diatomaceous earth in the composite is replaced by diatomaceous earth in equal amounts.

[0070] Comparative Example 4

[0071] An annealing technology for anchor chain steel, which differs from Example 1 in that the modified diatomaceous earth in the composite is replaced by sophorolipids in equal amounts.

[0072] Comparative Example 5

[0073] An annealing technology for anchor chain steel, which differs from Example 1 in that the modified diatomaceous earth in the composite is replaced by rhamnolipid in equal amounts.

[0074] Performance test

[0075] The following performance tests were performed on the anchor chain steels of Examples 1-13 and Comparative Examples 1-5:

[0076] Tensile strength: The tensile strength of the anchor chain steel was measured in accordance with DB32 / T4116-2021 "Technical Specification for Tensile Strength of Building Structural Steel by Leeb Hardness Tester Method". The test results are shown in Table 2.

[0077] Yield strength: The yield strength of anchor chain steel was measured according to JGJ107-2003 "General Technical Code for Mechanical Connection of Reinforcement Bars". The test results are shown in Table 2.

[0078] Elongation: The elongation of anchor chain steel was measured according to GB / T228-2002 “Room Temperature Tensile Test Method for Metallic Materials”. The test results are shown in Table 2.

[0079] Table 2 Test results

[0080]

[0081]

[0082] As can be seen from Table 2, an annealing technology for anchor chain steel of the present application, by cleaning the anchor chain steel before annealing to remove surface impurities of the anchor chain steel, better improves the mechanical strength of the anchor chain steel and improves the quality of the anchor chain steel, wherein the tensile strength is 861-937 MPa, the yield strength is 682-789 MPa, and the elongation is 24-45%.

[0083] Combining Example 1 and Comparative Examples 1-5, it can be seen that the tensile strength of the anchor chain steel in Example 1 is 861 MPa, the yield strength is 682 MPa, and the elongation is 24%, which is better than Comparative Examples 1-5, indicating that it is more appropriate to add a composite to the raw materials of the cleaning liquid, and it is more appropriate to compound the composite with sophorolipids, rhamnolipids and modified diatomaceous earth. Through the combined effect of the three, the cleaning effect of the anchor chain steel before annealing can be further improved, thereby helping to improve the quality of the anchor chain steel.

[0084] It can be seen from Examples 1-6 that other raw materials except the composite material have little effect on the anchor chain steel when they vary within a certain range.

[0085] Combining Example 5 and Examples 7-8, it can be seen that the tensile strength of the anchor chain steel in Example 7 is 904 MPa, the yield strength is 736 MPa, and the elongation is 30%, which is better than other examples, indicating that the amount of the composite added in Example 7 is more appropriate. If the amount of the composite added is too little, it will not have a better cleaning effect. If the amount of the composite added is too much, the amount of modified diatomaceous earth added will be too much, which will easily lead to agglomeration and affect the cleaning effect.

[0086] In combination with Example 7 and Examples 9-12, it can be seen that the tensile strength of the anchor chain steel in Example 11 is 925 MPa, the yield strength is 772 MPa, and the elongation is 40%, which are better than those of other examples, indicating that the composite prepared by Preparation Example 5 is more suitable and can better improve the quality of the anchor chain steel. If the amount of modified diatomaceous earth added is too much, agglomeration is likely to occur, which affects its function, so the amount of addition needs to be controlled.

[0087] Combining Example 11 and Example 13, it can be seen that the tensile strength of the anchor chain steel in Example 13 is 937 MPa, the yield strength is 789 MPa, and the elongation is 45%, which is better than Example 11, indicating that it is more appropriate to purify and pretreat sophorolipids and rhamnolipids before use. Purification of sophorolipids and rhamnolipids can improve the purity of the two, make it easier for the two to play a role, and improve the cleaning effect of the anchor chain steel. Reduce the impact on the annealing process, thereby helping to improve the quality of the anchor chain steel.

[0088] As described above, the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features thereof may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. An annealing technology for anchor chain steel, characterized in that: The following steps are involved: S1: putting the anchor chain steel into a cleaning solution for cleaning, then rinsing with water, and drying to obtain the cleaned anchor chain steel; S2: heat treating the anchor chain steel, first heating it to 300-400°C, keeping it warm, heating it to 550-750°C for the second time, keeping it warm, then heating it to 900-950°C, keeping it warm, quenching it with salt water to room temperature, then tempering it to 300-400°C, keeping it warm, tempering it to 500-600°C for the second time, keeping it warm, and water cooling it to obtain the heat-treated anchor chain steel; Among them, the cleaning solution in step S1 includes the following raw materials in parts by weight: 20-35 parts of sodium hydroxide, 5-9 parts of diethylenetriaminepentaacetic acid, 1-3 parts of sodium citrate, 1-5 parts of sodium gluconate, 6-12 parts of alcohol ether glycoside, 11-18 parts of the complex, and 150-200 parts of water, and the complex is a compound of sophorolipids, rhamnolipids and modified diatomaceous earth.

2. The annealing technology for anchor chain steel according to claim 1, characterized in that: The composite is prepared by the following method: putting modified diatomaceous earth into water, dispersing it by ultrasonication, and mixing it evenly to obtain a first mixed solution; putting sophorolipid into water, adding rhamnolipid, and mixing it evenly to obtain a second mixed solution; mixing the first mixed solution and the second mixed solution evenly, standing, filtering, washing, and drying to obtain the composite.

3. The annealing technology for anchor chain steel according to claim 2, characterized in that: The weight ratio of the sophorolipid, rhamnolipid and modified diatomaceous earth is 1:(0.8-1.3):(4-7).

4. The annealing technology for anchor chain steel according to claim 2, characterized in that: The modified diatomite is prepared by the following method: sodium hydroxide and aluminum hydroxide are put into water, mixed evenly, heated and reacted to obtain a mixed solution A; diatomite is put into water, mixed evenly, heated and reacted to obtain a mixed solution B; the mixed solution A and the mixed solution B are mixed evenly, heated and reacted, filtered, washed, and dried to obtain the modified diatomite.

5. The annealing technology for anchor chain steel according to claim 2, characterized in that: The sophorolipids and rhamnolipids are pretreated by the following method before use: sophorolipids and rhamnolipids are put into water, pH value is adjusted, temperature is increased, stirring is performed in a water bath, standing for stratification, taking out the lower layer, and repeating the above operation for multiple times to obtain pretreated sophorolipids and rhamnolipids.

6. The annealing technology for anchor chain steel according to claim 1, characterized in that: The specific cleaning process of the anchor chain steel in the cleaning liquid in step S1 is: first immersing for 5-10 minutes, and then swing washing for 1-5 minutes, wherein the swing frequency is 25-45 times / min, the round trip is 1 time, and the swing distance is 40-60mm.

7. The annealing technology for anchor chain steel according to claim 1, characterized in that: In step S2, the anchor chain steel is heat treated in an atmosphere of a protective gas, wherein the protective gas is hydrogen or nitrogen.

8. The annealing technology for anchor chain steel according to claim 1, characterized in that: The mass fraction of the brine in step S2 is 5-10%.